ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸šå¦ç”Ÿ2015å±Šä½¿ç”¨å¤åˆè¶‹å‘è¡¥è¯ â€œä¸‹æ¥â€ã€â€œä¸‹åŽ»â€ã€â€œä¸Šæ¥â€å’Œâ€œä¸ŠåŽ»â€çš„åè¯¯åˆ†æž - Chan, Su; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCompound directional complement is one of the most commonly syntactic expressions that are used in Mandarin, it is also the focus and the difficulty of Mandarin teaching. The Compound directional complement such as: â€œxialaiâ€, â€œxiaquâ€, â€œshanglaiâ€, â€œshangquâ€ are four words that commonly use in daily life as well. They have similarities and differences in semantics which make students often have errors in the use of Compound directional complement. The writer of the student of Mandarin education study program at Tanjungpura university teacher training and education faculty academic 2015 used the Compound directional complement such as: â€œxialaiâ€, â€œxiaquâ€, â€œshanglaiâ€, â€œshangquâ€ to conduct the test, to analyze students errors and find out their causes.Â From the results of the test, the writer concludes that students are using â€œxialaiâ€, â€œxiaquâ€, â€œshanglaiâ€, â€œshangquâ€ the error rate is: 39.90%, 44.19%, 34.34%, 44.44%. Students use the Compound directional complementsuch as: â€œxialaiâ€, â€œxiaquâ€, â€œshanglaiâ€, â€œshangquâ€ the reason for the error is the mother tongue and the target language.The writer hopes that this thesis can provide teaching basis for Mandarin teachers.Â Keywords: Compound directional complement, Errors analysis, Reasons for errors